The Significance of Digital Marketing Strategies for Continuity of SMEs - Ioseb Gabelaia; Lasha Tchelidze (International School for Social and Business Studies, 2022)
Purpose: Digital marketing trends change time from time; therefore, Small and Medium-sized enterprises often face challenges while adopting digital marketing strategies. These challenges are caused by the richness and complexity of tactics to optimize growth, customer engagement, buyer behaviors, and business continuity. This paper focuses on the significance of adopting digital marketing strategies through the 6W Marketing Model for the continuity of Small and Medium Size Enterprises (SMEs). To achieve this goal, the nature of digital marketing strategies for SMEs, such as content marketing, social media marketing, and email marketing, were analyzed. Study design/methodology/approach: A thematic literature review was conducted to explore the significance of digital marketing strategies for the continuity of SMEs. We synthesized the available literature that interconnects digital marketing developments with SMEs. The data was obtained through mixed, quantitative, and qualitative methods. Findings: The findings underlined the need and significance of digital marketing awareness for business continuity. Consequently, respondents recognized the role of the 6W marketing model to assist in making informed decisions on which type of digital marketing strategies to employ. Besides, this study ignores and does not consider specifics of the algorithms which give a content ranking. It is imperative to understand the role of these algorithms, how they work and how to deal with them to get the most out of the campaigns. Low-quality or relevancy scores will affect the campaign and bring lower results. Originality/value: This paper brings together the challenges and complexity of utilizing digital marketing strategies for SMEs' business continuity. Marketers always search for the best elements for strategic campaigns. Hence, based on the research, the 6W marketing model is proposed to understand better the impact of each digital marketing strategy on business continuity. Besides, the model presents a guide to strategically allocating financial and human resources.